Beliefs, evidence, and action towards the green energy transition - Mark Freeman; Benjamin Groom; Frikk Nesje; Gernot Wagner (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
We assess how changes in the scientific consensus around equilibrium climate sensitivity (ECS), as captured by the IPCC's Fifth (AR5) and Sixth (AR6) Assessment Reports, impact policymakers' willingness to take climate action, including through increasing subsidies to investments that will help to deliver the clean energy transition. Taking the IPCC's reports at face value, the ECS estimates in AR6 would have lowered a policymaker's willingness to act on climate relative to AR5 due to a narrower "likely" range. However, Bayesian updating may reverse this conclusion. An accuracy-motivated policymaker who was not convinced to take greater climate action by the evidence in AR5 may be more likely to increase their investment in clean energy by the evidence in AR6.
Keywords: D83; H51; Q48; Q54; 330; equilibrium climate sensitivity; Bayesian updating; climate policy